MOLECULAR CHARACTERIZATION AND BIOLOGICAL CONTROL POTENTIAL OF AN EGYPTIAN ISOLATE OF SCLEROTINIA SCLEROTIORUM MITOVIRUS 1 - Mahmoud E. Khalifa; Eldessoky S. Dessoky; Atef S. Sadik (Journal of Animal and Plant Sciences, 2022)
Several mycoviruses have potential to induce hypovirulence on their fungal pathogens and therefore the interest in mycoviruses has increased in recent years. In the current study, a single double-stranded RNA (dsRNA) molecule of 2531 nts was detected, sequenced and characterized from an Egyptian isolate (D7) of Sclerotinia sclerotiorum fungus. The dsRNA has one open reading frame (ORF), in its positive strand, encoding a protein with conserved motifs characteristic of viral RNA-dependent RNA-polymerases (RdRps). The RdRp encoded by the ORF shares 91.84% identity with that of isolate HC025 of sclerotinia sclerotiorum mitovirus 1 (SsMV1) and consequently it was tentatively named SsMV1-D7. As for previously described mitoviruses, the termini of the (+) strand of SsMV1-D7 RNA could potentially fold into stable secondary structures. Horizontal transmission and virulence experiments showed that SsMV1-D7 is probably responsible for the altered growth and virulence of S. sclerotiorum.
Keywords: dsRNA; Mycovirus; Mitoviridae; Mitovirus; Sclerotinia sclerotiorum; Hypovirulence